A populational based study on the prevalence of neonatal near miss in a city located in the South of Brazil: prevalence and associated factors - Guilherme Alberto Silva; Karin Alana Rosa; Elizabeth Schirin Farahani Saguier; Elisa Henning; Fatima Mucha; Selma Cristina Franco
Abstract Objectives: to identify the prevalence of neonatal near miss morbidity in the city of Joinville, SC and the associated factors. Methods: a populational based cross-sectional study including all live births in 2012 registered at SINASC. The near miss cases were identified based on the weight <1500g, Apgar scores at 5th minute <7, gestational age <32 weeks, use of mechanical ventilation or presence of congenital malformation. The gross odds ratios (OR) and its respective 95% confidence intervals (95% CI) were calculated and the logistic regression was performed to obtain the adjusted odds ratios and its respective 95% CI. Results: the prevalence of near miss was 33 per thousand live births (95% CI: 29-37). In the final model, a risk classification of live births according to the City Program (Programa Municipal) (ORaj= 19.7; 95% CI: 14.2 to 27.2), cesarean section (ORaj= 2.1; 95% CI:1.5 to 2.8) and public hospital (ORaj= 1.7; 95% CI: 1.2 to 2.3) remained associated to morbidity near miss. Conclusions: near miss morbidity was 7.3 times higher than neonatal mortality. To know its determinants in different national contexts may include some changes in the focus of public health actions by redirecting to preventive interventions.